2006
DOI: 10.1210/en.2005-1228
|View full text |Cite
|
Sign up to set email alerts
|

Endothelin-2 in Ovarian Follicle Rupture

Abstract: The ovulatory process is activated by a surge of LH, a pituitary gonadotropin, which initiates a cohort of dramatic changes in biochemical, physical, and gene expression in the ovary, leading to follicle rupture and oocyte release. Here we report the identification of endothelin-2 (EDN2) as a last moment-trigger of follicle rupture. In the ovary, EDN2 is exclusively and transiently expressed in the granulosa cells immediately before ovulation. Administration of EDN2 to the ovarian tissue induced rapid contract… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

16
164
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 113 publications
(183 citation statements)
references
References 32 publications
16
164
0
Order By: Relevance
“…Changes in intra-follicular pressure are observed as early as midway through the periovulatory cascade (Matousek et al 2001), coincident with increases in factors affecting vascular permeability (Gómez et al 2003;Kitajima et al 2004;Miyabayashi et al 2005) and the array of proteolytic enzymes known to be integral to the breakdown of the extracellular matrix before ovulation (reviewed in Curry and Smith 2006). In contrast, expression of mRNA for Edn2 is only increased very late in the periovulatory period, ∼12 h after the induction of ovulation with hCG in the rat (Ko et al 2006), well after the first observed changes in intra-follicular pressure. Therefore, we propose that the contractile action of EDN2 would be imposed at the time of ovulation itself, upon an already weakened follicular structure, resulting in no change or an actual decrease in intra-follicular pressure (as the follicle ruptures), consistent with the follicular pressure profiles described over 40 years ago by Rondell (1964).…”
Section: Introductionmentioning
confidence: 89%
See 4 more Smart Citations
“…Changes in intra-follicular pressure are observed as early as midway through the periovulatory cascade (Matousek et al 2001), coincident with increases in factors affecting vascular permeability (Gómez et al 2003;Kitajima et al 2004;Miyabayashi et al 2005) and the array of proteolytic enzymes known to be integral to the breakdown of the extracellular matrix before ovulation (reviewed in Curry and Smith 2006). In contrast, expression of mRNA for Edn2 is only increased very late in the periovulatory period, ∼12 h after the induction of ovulation with hCG in the rat (Ko et al 2006), well after the first observed changes in intra-follicular pressure. Therefore, we propose that the contractile action of EDN2 would be imposed at the time of ovulation itself, upon an already weakened follicular structure, resulting in no change or an actual decrease in intra-follicular pressure (as the follicle ruptures), consistent with the follicular pressure profiles described over 40 years ago by Rondell (1964).…”
Section: Introductionmentioning
confidence: 89%
“…Granulosa cells were isolated from ovaries collected before rats were treated with PMSG, 48 h after PMSG and 12 h after hCG (n = 3 animals per time point), as described previously (Ko et al 2006). Total RNA was extracted from granulosa cells with TRIzol (Invitrogen Corp., Carlsbad, CA, USA), according to the manufacturer's directions and the integrity verified by visualisation of distinct 18S and 28S rRNA bands after ethidium bromide staining in an agarose gel.…”
Section: Real-time Pcr Analysismentioning
confidence: 99%
See 3 more Smart Citations